2008
DOI: 10.1158/0008-5472.can-07-3140
|View full text |Cite
|
Sign up to set email alerts
|

Raf and MEK Protein Kinases Are Direct Molecular Targets for the Chemopreventive Effect of Quercetin, a Major Flavonol in Red Wine

Abstract: Considerable attention has focused on the health-promoting effects of red wine and its nonflavonoid polyphenol compound resveratrol. However, the underlying molecular mechanisms and molecular target(s) of red wine or other potentially active ingredients in red wine remain unknown. Here, we report that red wine extract (RWE) or the red wine flavonoid quercetin inhibited 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced transformation of JB6 promotion-sensitive mouse skin epidermal (JB6 P+) cells. The activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 178 publications
(127 citation statements)
references
References 32 publications
6
119
0
2
Order By: Relevance
“…The mixture was washed three times with 0.1 M acetated (pH 4.0) buffer and 0.1 M Tris buffer (pH 8.0), respectively, and suspended in PBS. In vitro pulldown assay was performed as described previously (27). Briefly, Histagged active IR protein (0.2 g) was incubated with piceatannol-Sepharose 4B or control Sepharose 4B beads.…”
Section: Methodsmentioning
confidence: 99%
“…The mixture was washed three times with 0.1 M acetated (pH 4.0) buffer and 0.1 M Tris buffer (pH 8.0), respectively, and suspended in PBS. In vitro pulldown assay was performed as described previously (27). Briefly, Histagged active IR protein (0.2 g) was incubated with piceatannol-Sepharose 4B or control Sepharose 4B beads.…”
Section: Methodsmentioning
confidence: 99%
“…Luteolin (20) and apigenin (21) were able to inhibit PKC and PI3K/Akt in various prostate cancer cell lines [47,48]. Quercetin (22) was reported to inhibit MEK1, Raf1 and PKC and, thus, inhibit neoplastic cell transformation (Table 3) [48,60]. Myricetin (23) was also capable of inhibiting MEK1 but the inhibition was more potent with the MAP kinase 4 (MKK4) ( Table 3) [49].…”
Section: Group Iii: Flavonoids and Their Analoguesmentioning
confidence: 99%
“…Quercetin (22) was docked to a separate site, adjacent to the ATP-binding site of mitogen-activated protein kinase/extracellular signal-regulated kinase (MEK1) [60]. This binding event results in stabilization of the inactive conformation of the activation loop of MEK1 [60].…”
Section: Polyphenol Structure-activity Rela-tionships (Sar) With Respmentioning
confidence: 99%
“…Research directed toward elucidating underlying molecular mechanisms of chemoprevention or chemoprotection with edible phytochemicals present in fruits, vegetables, spices, and herbs has recognized distinct redox-sensitive transcription factors and their upstream regulators as potential targets (35). Research findings from The Hormel Institute have shown that blocking certain cellular signals with natural small molecule inhibitors can decrease UV-induced skin carcinogenesis and other cancers (32,33,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Promising Agents and Targetsmentioning
confidence: 99%